Low dose bitter leaf improves sperm quality disrupted in immunosuppressed Wistar rats: An experimental study - Risikat Eniola Kadir; Abdulmumin Ibrahim; Balkis Abimbola Ibrahim; Sadiya Musa Gwadabe; Rukayat Jaji-Sulaimon; Munirat Foyeke Adigun; Adeoye Oyetunji Oyewopo (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Synthetic prednisolone (PRED) is a widely used over-the-counter glucocorticoid. Glucocorticoids have inhibitory effects on the immune system and are often used as immunosuppressive agents. Suppressed immunity may impact fertility via the hypothalamic-pituitary-adrenal axis. Bitter leaf (BL) has been shown to improve sperm parameters, but its effects on immunosuppression-associated infertility have not yet been documented. Objective: To determine the fertility effects of bitter leaf on immunosuppressed Wistar rats. Materials and Methods: A total of 30 male adult Wistar rats were randomly assigned to 6 groups (n = 5/each). Group A served as a control and were given distilled water in addition to normal feeds, group B received 2 mg/kg PRED for 14 days and served as the standard immunosuppressed group, and groups C-F were immunosuppressed as in B but in addition received 50 mg/kg levamisole, low-dose (250 mg/kg) BL, high-dose (375 mg/kg) BL, and low-dose BL + levamisole, respectively. The CD4 counts, hematological parameters, and sperm parameters were analyzed and compared. Results: There were significant decreases in sperm motility, progressive motility, morphology, and life/death ratio in the animals given PRED only compared to the controls (p = 0.002, 0.001, 0.001, and 0.01, respectively). These were significantly increased in the treated groups, and animals given levamisole and 250 mg/kg BL showed significantly increased sperm counts compared to the controls (p = 0.04 and p = 0.04, respectively). Conclusion: Low-dose BL (250 mg/kg) restored the sperm parameters altered by prednisolone administration.